An Employer-Based Evaluation of the Job Performance of Bachelor of Science in Hospitality Management Graduates - Diyah Guwen Alejandrino (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: This study aimed to evaluate the job performance of Bachelor of Science in Hospitality Management graduates of Kalinga State University as assessed by their employers. Methodology: This study employed the survey research method and descriptive research design to assess the job performance of BS Hospitality Management graduates. The respondents consisted of owners, managers, and supervisors of 75 graduates from the academic years 2017–2020. Data were collected through the administration of a standardized questionnaire whose validity and reliability had been previously established, ensuring the accuracy and consistency of the responses obtained from the participants. Main Findings: The majority of Bachelor of Science Hospitality Management graduates are regularly employed (47%), mostly in entry-level positions within 5–8 months of service (48%). Employer evaluations of 75 respondents revealed that graduate performance generally met expectations across all five job criteria: abilities, knowledge, and skills (60%); judgment and analysis (75%); communication skills (73%); leadership skills (75%); and attitude and behavior (62%). However, specific areas including accountability, advanced communication, and initiative were rated unacceptable by 7–10% of employers. Novelty/Originality of this study: This study advances existing knowledge by providing localized, employer-based evidence on the job performance of hospitality management graduates from a state university. Unlike generalized graduate studies, it identifies specific performance gaps in accountability, communication, initiative, and leadership, offering actionable recommendations for curriculum enhancement. By centering the employer's perspective over self-reported competencies, the study introduces a more objective lens in assessing graduate outcomes. Furthermore, its five-criteria performance framework with quantified ratings establishes a measurable institutional baseline for tracking graduate performance improvements in future studies.